Prevalence of golf-related injuries among recreational golfers: a preliminary finding / Amy Nurul Azielah ... [et al.] - Azielah, Amy Nurul; Danis, Ajau; Masuri, Mohamad Ghazali; Md Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Despite knowing that golf is a non-contact sport, injury can be a nightmare for its enthusiast. Golf is a game that can be played professionally or as a hobby or for recreational purposes. Although golf is played by many peoples in this country, however, there is few of studies to determine golf-related injuries, especially among recreational golfers. Hence, the objective of the study was to investigate the prevalence of golf-related and type of injuries among recreational golfers. An online retrospective cross-sectional study was done among 327 respondents in collaboration with various golf clubs in Malacca. The inclusion criteria for this study were an active recreational golfer that playing golf for more than a year, and age 18 years old and above. Meanwhile, the study excludes those golfers that are currently having a musculoskeletal disease such as osteoarthritis and rheumatoid arthritis. Data were analysed by using SPSS 22.0 and descriptively described by using frequency. A Pearson’s Chi-Square test was used to analyze the relationships between variables of study. The results show that the prevalence of injury was 44.3%. Meanwhile, the most common injuries were the upper limbs (31.1%), back and abdomen (27.9%), and lower limbs (21.3%). The results revealed that age was statistically significant with that of golf injuries (p-value =0.04). In conclusion, as a non-contact sport, and as in any sports or game, injury is the most feared enemy, and golf is not spared. Further study is warranted among professional golfers to establish the effect of injury on their performance.